2011
DOI: 10.1111/j.1600-051x.2011.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter-generational continuity in periodontal health: findings from the Dunedin Family History Study

Abstract: Objective To determine whether parental periodontal disease history is a risk factor for periodontal disease in adult offspring. Methods Proband periodontal examination (combined attachment loss (CAL) at age 32, and incidence of CAL from ages 26–32) and interview data were collected during the age-32 assessments in the Dunedin Study. Parental data were also collected. The sample was divided into two familial-risk groups for periodontal disease (high- and low-risk) based on parents’ self-reported periodontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…In most cases, use of proportions instead of raw numbers provided higher AUC and Sen + Spec value (Table 3, http://www.joponline.org/doi/suppl/10.1902/jop.2017.160607/suppl_file/160607_suptab3.pdf in online Journal of Periodontology ). In such a young population, the more conservative approach as cutoff point to determine presence of periodontal disease (e.g., CAL ≥3 mm in the Beck et al 31 classification and the Baelum and López 16 adolescents classification instead of CAL ≥4 mm in the Shearer et al 13 classification) yields higher AUC and Sen + Spec value (Table 3, http://www.joponline.org/doi/suppl/10.1902/jop.2017.160607/suppl_file/160607_suptab3.pdf in online Journal of Periodontology ). Also, prediction of more severe cases provided more accurate results, as observed in van der Velden 11 and Shearer et al 13 classifications (see http://www.joponline.org/doi/suppl/10.1902/jop.2017.160607/suppl_file/160607_suptab3.pdf in online Journal of Periodontology ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, use of proportions instead of raw numbers provided higher AUC and Sen + Spec value (Table 3, http://www.joponline.org/doi/suppl/10.1902/jop.2017.160607/suppl_file/160607_suptab3.pdf in online Journal of Periodontology ). In such a young population, the more conservative approach as cutoff point to determine presence of periodontal disease (e.g., CAL ≥3 mm in the Beck et al 31 classification and the Baelum and López 16 adolescents classification instead of CAL ≥4 mm in the Shearer et al 13 classification) yields higher AUC and Sen + Spec value (Table 3, http://www.joponline.org/doi/suppl/10.1902/jop.2017.160607/suppl_file/160607_suptab3.pdf in online Journal of Periodontology ). Also, prediction of more severe cases provided more accurate results, as observed in van der Velden 11 and Shearer et al 13 classifications (see http://www.joponline.org/doi/suppl/10.1902/jop.2017.160607/suppl_file/160607_suptab3.pdf in online Journal of Periodontology ).…”
Section: Resultsmentioning
confidence: 99%
“…Periodontal disease classifications for epidemiologic studies were developed for population‐based designs with a wide range of age groups. Thus, to demonstrate possible differences among classifications, six different classifications were used as outcomes (see http://www.joponline.org/doi/suppl/10.1902/jop.2017.160607/suppl_file/160607_suptab2.pdf in online Journal of Periodontology ) 11‐13,15,16,31 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is consistent with Shearer et al . . who showed that the children of parents with poor periodontal oral health are themselves more likely to have poor periodontal health.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatrician Thomas Boyce and colleagues studying 5-year old children have demonstrated how psychosocial, infectious, and stress-related processes seem to converge in the development of caries and thus contribute to increasing the risk that future, overall dental health be impaired [13]. The highly acknowledged, prospective Dunedin Study from New Zealand, which followed the impact of psychosocial distress on children over a period of years, has shown a clear correlation between the dental health of the children and that of their parents, reflecting social gradients [88]. In a recent US study, allostatic load, impaired dental health, and low sociocultural status have also been shown to be associated [12].…”
Section: Discussionmentioning
confidence: 97%